HUBUNGAN HASIL BELAJAR AKUNTANSI DENGAN HASIL BELAJAR MATEMATIKA SISWA JURUSAN IPS SMA 1 SERASAN - ., Rosita; Buwono, Sri; ., Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The title of this thesis is the Relationship with the Accounting Learning Outcomes Student Learning Outcomes Mathematics Department IPS SMA 1 Serasan. This study aimed to determine whether there is a relationship between the learning outcomes of accounting with the results of studying math and to know how much to do and find out what direction the relationship. The method used in this research is a qualitative descriptive quantitative method. With the form of research is the study of the relationship (Interrelation studies). From the results of data processing accounting relationship between learning outcomes with students majoring in mathematics learning outcomes IPS in SMA Negeri 1 Serasan. Through the formulation of percentage can be concluded that there is a relationship between the learning outcomes of accounting with the results of students' learning of mathematics majors IPS SMA Negeri 1 Serasan and can be categorized as moderate or sufficient. While the results of the analysis of data obtained through the Product Moment Correlation r results count is greater than the table r r r count equal to 0.346 and 0.325 table or count 0.346 r> 0.325 r table can be considered moderate or sufficient Keywords: Accounting and Mathematics Learning Outcomes Abstrak : Judul Skripsi ini adalah Hubungan Hasil Belajar Akuntansi dengan Hasil Belajar Matematika Siswa Jurusan IPS SMA 1 Serasan. Penelitian ini bertujuan untuk mengetahui apakah terdapat hubungan antara hasil belajar akuntansi dengan hasil belajar matematika dan untuk mengetahui seberapa besar hubungannya serta bagaimana arah hubungannya. Metode yang digunakan dalam penelitian ini adalah metode deskriptif kualitatif kuantitatif. Dengan bentuk penelitiannya adalah studi hubungan (Interrelation studies). Dari hasil pengolahan data hubungan antara hasil belajar akuntansi dengan hasil belajar matematika siswa jurusan IPS di SMA Negeri 1 Serasan. Melalui perumusan Presentase dapat ditarik kesimpulan bahwa terdapat hubungan antara hasil belajar akuntansi dengan hasil belajar matematika siswa jurusan IPS SMA Negeri 1 Serasan dan dapat dikategorikan sedang atau cukup. Sedangkan dari hasil analisis data melalui Korelasi Product Moment diperoleh hasil r hitung lebih besar dari r tabel yaitu r hitung sebesar 0,346 dan r tabel 0,325 atau r hitung 0,346 > r tabel 0,325 dapat dikategorikan sedang atau cukup. Kata Kunci: Hasil Belajar Akuntansi, Hasil Belajar Matematika